Description of Visfatin Adipokine and its Roles on Inflammation and Coronary Heart Disease: A Review Study - Al-Kraity, Assist. Prof. Dr. Wijdan Rajh Hamza; Faisal, Ali Hussein; Khaleel, Ali Nabeel; Naeaam, Mahmoud Tuama; Jabar, Ali Sattar (Medical Science Journal for Advance Research, 2021)
Coronary heart disease (CHD) is a generic designation for a group of related syndromes resulting from myocardial ischemia – an imbalance between cardiac blood supply (perfusion) and myocardial oxygen demand. Visfatin (VF) is a recently discovered adipokine with different functions, Visfatin is mainly found in visceral adipose tissue and mimics insulin in lowering plasma glucose levels and, Visfatin emerges as a player in the development and progression of atherosclerotic lesions by directly promoting smooth muscle cell proliferation, Aberrant angiogenesis is now considered a feature of the atherogenic process in both coronary and carotid diseases. This adipokine was previously known as a pre-B-cell colony-enhancing factor (PBEF) or Nicotinamide phosphoribosyltransferase (NAmPRTase or Nampt) an enzyme that in humans is encoded by the NAMPT gene and demonstrated to be an intracellular protein with a key enzyme role in nicotinamide adenine dinucleotide (NAD)